PENGARUH PENEMPATAN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. LARAS PRIMA SAKTI CABANG SELUMA - Erwin Mudzil Al Khaafidh; Marliza Ade Fitri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This research is based on the importance of a sense of employee performance in achieving company goals. Factors that can affect employee performance include work placement, work environment, and work motivation. The purpose of this study was to determine the effect of work placement, work environment and work motivation on the performance of employees at PT. Laras Prima Sakti, Seluma branch. This study uses a quantitative approach. Quantitative research method is research that is systematic, structured, and composed from the beginning to the end of the research. The population in this study are employees of PT. Laras Prima Sakti Seluma branch and sampling using the Saturated Sample method. Based on multiple linear regression, we get the form of the regression equation Y=49.021+0.301X1+0.462X2+0.285X3 and the magnitude of this effect can be seen from the coefficient of determination or R Square (R2) = 0.532, which is 53.2% while the remaining is 46.8%. influenced by other variables outside the research. Furthermore, work placement has a significant effect on employee performance. This is supported by the results of Multiple Linear Regression of 0.301, and the work environment has a significant effect on employee performance. This is supported by the results of Multiple Linear Regression of 0.462, and work motivation has a significant effect on employee performance. This is supported by the results of Multiple Linear Regression of 0.285. with a probability (sig) of 0.000 <alpha 0.05 has a value of Fcount Fcount > Ftable (0.000 > 3.14). As well as work placement, work environment and work motivation partially have a significant effect on employee performance with a probability value (sig) of each variable, namely work placement (X1) with probability (sig) 0.011 <alpha 0.05 has a value of tcount> ttable (2.648 >1.999), work environment variable (X2) with probability (sig) 0.041 <alpha 0.05 has a tcount > ttable (2.095 >1.999), work motivation variable (X3) with probability (sig) 0.020 <alpha 0.05 has tcount > ttable (2.401 > 1.999). Keywords: work placement, work environment, work motivation, employee performance